2019
DOI: 10.3233/mnm-190322
|View full text |Cite
|
Sign up to set email alerts
|

Irisin, leptin and adiponectin levels are reduced significantly during fasting

Abstract: BACKGROUND: Ramadan fasting involves refraining from food and liquids from the sunrise till sunset for one month yearly; affecting the sleep pattern and duration, physical activity, and meal number and composition leading to biochemical and physiological changes in the body. Irisin, adiponectin, and leptin induce multiple metabolic effects. OBJECTIVE: The aim of this study is to examine the effect of the Ramadan fasting on serum levels of irisin, adiponectin, and leptin. MATERIALS AND METHODS: A total of sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Several clinical studies reported a significant decrease serum irisin levels in T2DM patients [35,36], despite the fact that the current study didn't assess serum irisin levels in T2DM patients and controls. The only research conducted in Jordan reported a significant decrease in the levels of irisin during Ramadan compared to prior to Ramadan (33.6 vs. 16.3; P = 0.003) in a group of healthy subjects [37].…”
Section: Discussionmentioning
confidence: 82%
“…Several clinical studies reported a significant decrease serum irisin levels in T2DM patients [35,36], despite the fact that the current study didn't assess serum irisin levels in T2DM patients and controls. The only research conducted in Jordan reported a significant decrease in the levels of irisin during Ramadan compared to prior to Ramadan (33.6 vs. 16.3; P = 0.003) in a group of healthy subjects [37].…”
Section: Discussionmentioning
confidence: 82%
“…Subsequent research demonstrated that irisin levels are positively correlated with fruit consumption and negatively with meat eating [ 23 ], whereas others showed that increased energy intake results in a reduction in irisin levels [ 24 ]. In one study including individuals practicing Ramadan fasting—a type of religious fasting which involves no eating and drinking from sunrise to sunset—Alzoughool et al demonstrated decreased irisin profiles after fasting compared with pre-fasting values [ 25 ]. In a cohort of individuals with metabolic syndrome who underwent an energy-restricted program, weight loss was accompanied by a depletion in irisin levels, which correlated with the reduction in atherogenic-related lipid parameters, independently of changes in BW [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that fasting in Ramadan attenuates inflammation and is beneficial to metabolic health. Alzoughool et al [9] examined the effect of RF on additional metabolic parameters such as serum levels of irisin, adiponectin, and leptin in healthy students. All levels significantly reduced after Ramadan, with irisin levels significantly correlating with the physical activity level of participants.…”
Section: Physiological Changes In Healthy Individualsmentioning
confidence: 99%